Risk Factors and Welfare Determinants Among Small-Scale Fish Processing Communities in Kupang City - Arianty, Devi; Hasan, Sari Zulfiana; koten, Vebiana Rosari Timu (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2026)
The Oesapa coastal area in Kupang City is a community-based fish landing site utilized for fish processing activities; however, its utilization has not been optimal, thereby affecting the welfare of fish-processing communities. This study aims to analyze the factors influencing the welfare of Small-Scale Fish Processing Communities and to identify the dominant factors that take priority in a risk management framework. The methods used include multiple linear regression to analyze the factors affecting the community welfare, while the House of Risk (HOR) was used to identify and prioritize risk sources. The regression showed that the welfare of fish-processing communities was significantly influenced by ecological, technological, social, and economic factors, with the regression equation Y = 7.354 + 0.136x₁ + 0.394x₂ + 0.099x₃ + 0.613x₄. Risk identification resulted in  16 risk events and 30 risk agents. HOR Phase 1 identified 20 priority risk agents, which were subsequently translated into 15 mitigation strategies. Furthermore, the ETD values obtained from HOR Phase 2 indicated that conducting regular fish processing training based on appropriate technology (P3) was the mitigation strategy with the highest (ETD) value. These findings provide a basis to establish priorities for more targeted risk mitigation programs aimed at improving the welfare of fish-processing communities.